Natural Bcl-2 inhibitor (−)– gossypol induces protective autophagy via reactive oxygen species–high mobility group box 1 pathway in Burkitt lymphoma. Issue 10 (October 2013) - Ni, Zhenhong; Dai, Xufang; Wang, Bin; Ding, Wen; Cheng, Panke; Xu, Liang; Lian, Jiqin; He, Fengtian
Abstract (−)– Gossypol, a natural inhibitor of anti-apoptotic Bcl-2 proteins, has presented an effective anti-tumor activity in numerous preclinical trials. More and more evidence in vivo and in vitro validates that (−)– gossypol can dramatically suppress cell proliferation and induce cell death in hematological malignancies. However, the detailed mechanisms are not well known. In the present study, we showed that treatment with (−)– gossypol stimulated reactive oxygen species (ROS) generation and induced autophagy in Burkitt lymphoma cells. Antioxidant N-acetyl-cysteine (NAC) pretreatment attenuated (−)– gossypol-induced autophagy. Furthermore, (−)– gossypol treatment increased the translocation of high mobility group box 1 (HMGB1) from nuclei to cytoplasm, which can be suppressed by NAC pretreatment. NAC pretreatment also dramatically enhanced (−)– gossypol-induced apoptosis and total cell death. These results indicate that (−)– gossypol induces a protective autophagy in Burkitt lymphoma cells, partly due to ROS induction and cytosolic translocation of HMGB1. Antioxidants may serve as potent chemosensitizers to enhance cell death through blocking (−)– gossypol-induced autophagy.